2012
DOI: 10.1186/1471-2466-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health status in COPD. A head-to-head comparison between the COPD assessment test (CAT) and the clinical COPD questionnaire (CCQ)

Abstract: BackgroundHealth status provides valuable information, complementary to spirometry and improvement of health status has become an important treatment goal in COPD management. We compared the usefulness and validity of the COPD Assessment Test (CAT) and the Clinical COPD Questionnaire (CCQ), two simple questionnaires, in comparison with the St. George Respiratory Questionnaire (SGRQ).MethodsWe administered the CAT, CCQ and SGRQ in patients with COPD stage I-IV during three visits. Spirometry, 6 MWT, MRC scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
144
5
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(165 citation statements)
references
References 27 publications
8
144
5
8
Order By: Relevance
“…Results of these studies indicated that there is strong evidence for the questionaries' content validity, internal consistency and correlation with similar instruments. In another study in Netherlands, the CAT, CCQ and SGRQ were completed by 90 COPD patients in stage I-IV during three visits and compared with each other [16]. This study showed that the CAT and CCQ both had acceptable validity, reliability and repeatability.…”
Section: Discussionmentioning
confidence: 90%
“…Results of these studies indicated that there is strong evidence for the questionaries' content validity, internal consistency and correlation with similar instruments. In another study in Netherlands, the CAT, CCQ and SGRQ were completed by 90 COPD patients in stage I-IV during three visits and compared with each other [16]. This study showed that the CAT and CCQ both had acceptable validity, reliability and repeatability.…”
Section: Discussionmentioning
confidence: 90%
“…The former changes are also clinically important since the minimum clinically important difference has been reported to range between 2-3.76 points [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…CAT appears to behave the same way across countries [20]. The minimum clinically important difference has been estimated to range between 2 [21] to 3.76 [22,23] points.…”
Section: Introductionmentioning
confidence: 99%
“…The MCID is defined as "the smallest difference in a measurable clinical parameter that indicates a meaningful change in the condition for better or for worse, as perceived by the patient, clinician or investigator" (70). A MCID is also frequently used to perform a sample size calculation, assess the efficacy of specific therapies and to assist in interpreting statistical significant results (71,72). To estimate a MCID, anchor-and distribution-based approaches can be applied (71).…”
Section: Treatmentmentioning
confidence: 99%
“…A MCID is also frequently used to perform a sample size calculation, assess the efficacy of specific therapies and to assist in interpreting statistical significant results (71,72). To estimate a MCID, anchor-and distribution-based approaches can be applied (71). Multiple studies looked at MCIDs for health status questionnaires.…”
Section: Treatmentmentioning
confidence: 99%